Otimismo da vontade, pessimismo da razão: English marxism, Anderson translation & integral journalism of New Left Review (or an international world-marxism in the street-fighting years of western europe) - Della Santa, Roberto [UNESP] (2015)
The following thesis deals with a certain kind of English Marxism, political-editorial activity of Perry Anderson and the integral journalism of the journal of ideas NEW LEFT REVIEW. Its conductive hypothesis is that the milieu of the so-called second generation of this New Left produced a genre of an internationalist «World-Marxism» in the street-fighting years (T. Ali) of Western Europe. The historical making of this intellectual project inserted in its cultural formation is a social process that gave birth to a coeval and coextensive doubledcharacter mediation activity: i) translation-form, i.e., insularization / particularization / nationalization of a continental socialist culture (France/Germany/Italy/Russia) in the Islands (UK) and, hence, ii) the journalism-form, or, its continentalization / universalization / internationalization of a sui generis kind of Marxism, consubstantieted in a nexus of identitydiversity on local and global. The contrasts and conclusions and predictions and performances necessarily deals with the genesis, development and metamorphosis of historians of social processes and critics of ideas such as Edward Palmer Thompson, Raymond Henry Williams and Eric John Hobsbawm vis-à-vis the intellectual group of Perry Anderson, Robin Blackburn & Tom Nairn. A history against the grain (W. Benjamin) imposes us the challenge of unrevealing the adjudicated consciousness that made the mediocre and inert socialist culture of Great-Britain the Liviest Republic of Letters of Contemporary Marxism in the last quarter of the Twentieth Century. The aphorism of «Pessimism/Optimism» reflected/refracted the history of NLR: beyond political common sense and before theoretical high abstraction is in order to repair the prism of NLR itself at the light of historical time. A critical revaluation of the ... - (Complete abstract click electronic access below)